Editorial - Perniola, Michele; Roggero, Pier Paolo; Casler, Michael D.; Cammarano, Davide; Rinaldi, Michele (Italian Journal of Agronomy, 2020)
The Italian Society of Agronomy (SIA) has changed the Editor in Chief and the Editorial board of the Italian Journal of Agronomy (IJA). The new Editorial board is being integrated with new expertise and includes three Associate editors: Michael D. Casler from USDA-ARS, USA, Davide Cammarano from Purdue University, USA and Michele Rinaldi from Council for Agricultural Research and Economics, Italy, the former co-editor. The Editorial board is redeveloping the Journal with a more pro-active publishing policy, that is consistent to the changing editorial demand of agronomy scientists worldwide. The international scientific publishing industry is facing a sharp transition, pulled by the increasing demand of rapid publication in the publish-or-perish or highly-cited paradigm and pushed towards full open access publishing by research funders and end-users. Minimizing the time between manuscript submission and paper publication is threatening the quality of the peer-review process, which is constrained by time pressure on highly qualified scientists, who end up being overloaded with reviews and editorial duties. The open access scientific journal industry is struggling between increasing the impact factor/cite score of the journals and maximizing the number of published articles, which is directly proportional to the publisher’s business. This is generating an increasing number of open access scientific publications worldwide: +75% between 2008-10 and 2015-17 in the ‘Agronomy and crop science’ subject category (Source: Scopus) while the non-open access publications in the same domain and time span increased by only +27%. This situation and the evolution of long term open-theme research funding schemes into short-term projectified finalized research funding programs are deeply influencing the topics of research in Agronomy. Long term agronomic facilities and field scale research are becoming rare and are often being replaced by short-term easily-published studies. However, international scientific exchanges are facilitating the development of permanent regional and global networks of researchers (e.g. AgMip, Global Research Alliance) that are developing unprecedented long-term research efforts on global issues around agronomy, involving hundreds of post-docs and young researchers worldwide. In this developing context, the Italian Journal of Agronomy, own by the Italian Society of Agronomy, a non-profit scientific organization, is developing a new editorial policy to contribute to the progress of agronomic science through an open-access, low-cost and authoritative scientific literature space, with particular attention to young scientists. There are number of reasons why an agronomy scientist should publish an article in the Italian Journal of Agronomy, including: i) to get a rapid and careful peer review assessment of the submissions by an authoritative editorial board with specific expertise in Agronomy and receive careful support on how to address major revisions when required; ii) to ensure maximum visibility for published articles through the open access system; iii) to contribute to the agronomic scientific literature through an open access Scopus/WOS scientific Journal owned by a non-profit scientific society at a fair price; iv) to compete for the SIA grants and prizes for best articles or best reviewers of the year. The new editorial policy of IJA includes a more pro-active publishing strategy aiming at widening the arena of international scientists contributing to the journal’s scope, including invited papers and special conditions for the publication of special issues on cutting-edge agronomy topics, promotion of the journal during scientific conferences and events, rewarding of the best articles and peer-reviewers contributing to the journal’s development. IJA is solely focused on the free diffusion of agroecosystem science, not on any other business: we trust that authors and readers will appreciate that IJA’s editorial board members work toward this mission without compensation and that the article fee is necessary only to cover the publisher’s net costs. We are very grateful to the past and new Editorial board and all peer reviewers for their invaluable contribution to the development of our Journal. Michele Perniola, President of the Italian Society of Agronomy Pier Paolo Roggero, Editor in Chief Michael D. Casler, Associate Editor Davide Cammarano, Associate Editor Michele Rinaldi, Associate Editor